2013
DOI: 10.4172/jbb.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Gentamicin C after IV, IM, SC and Oral Administration , C , C 1 1a and C 2 in Broiler Chickens 2a

Abstract: The pharmacokinetics and bioavailability of four major gentamicin components (C 1 , C 1a , C 2 and C 2a ) in chicken plasma administered at 5 mg/kg body weight by different routes of administration (IV, IM, SC and oral) was determined using reversed-phase high performance liquid chromatography (RP-HPLC) and pre-column derivatization with Phenylisocyanate (PIC). All the components, except for C 1a were well absorbed (bioavailability of 60% or greater) following administration by the IM and SC routes. The bioava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The PK of gentamicin has been studied in several species, including dogs [1], horses [2], chickens [10], fish [11], cats [13], pigs [14], sheep [15], calves [16], and buffalo calves [17]. Other than a single PK study reported several decades ago that used the intravenous (IV) route of administration [14], there are no gentamicin PK studies in piglets after the commonly used intramuscular (IM) or oral routes of administration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PK of gentamicin has been studied in several species, including dogs [1], horses [2], chickens [10], fish [11], cats [13], pigs [14], sheep [15], calves [16], and buffalo calves [17]. Other than a single PK study reported several decades ago that used the intravenous (IV) route of administration [14], there are no gentamicin PK studies in piglets after the commonly used intramuscular (IM) or oral routes of administration.…”
Section: Introductionmentioning
confidence: 99%
“…Human and animal studies have indicated that different components of gentamicin possess different potentials for toxicity, with some studies attributing the observed ototoxicity and nephrotoxicity of gentamicin mainly to the C 2 component [7][8][9]. Various levels of the different components contained in different gentamicin formulations, as well as significant differences observed in some pharmacokinetic parameters between different gentamicin components, could have clinical or toxicological implications [9,10]. However, reported differences in the pharmacokinetics (PK) of gentamicin components are not consistent across species [2,[10][11][12], emphasizing the importance of conducting PK studies of gentamicin components in species of interest such as piglets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation